2016
DOI: 10.1098/rsif.2016.0136
|View full text |Cite
|
Sign up to set email alerts
|

Gradual conversion of cellular stress patterns into pre-stressed matrix architecture during in vitro tissue growth

Abstract: The complex arrangement of the extracellular matrix (ECM) produced by cells during tissue growth, healing and remodelling is fundamental to tissue function. In connective tissues, it is still unclear how both cells and the ECM become and remain organized over length scales much larger than the distance between neighbouring cells. While cytoskeletal forces are essential for assembly and organization of the early ECM, how these processes lead to a highly organized ECM in tissues such as osteoid is not clear. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 74 publications
3
61
0
Order By: Relevance
“…The total amount of tissue formed was dependent on the channel perimeter and was proportional to the local curvature. Other studies have also shown that the tissue growth rate was highly dependent on curvature [6,7,15]. Curvature sign was also found to be important, showing decreasing tissue growth from concave (negative curvature) to convex ( positive curvature) to flat (zero curvature) surfaces [6,[15][16][17].…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…The total amount of tissue formed was dependent on the channel perimeter and was proportional to the local curvature. Other studies have also shown that the tissue growth rate was highly dependent on curvature [6,7,15]. Curvature sign was also found to be important, showing decreasing tissue growth from concave (negative curvature) to convex ( positive curvature) to flat (zero curvature) surfaces [6,[15][16][17].…”
Section: Introductionmentioning
confidence: 81%
“…Another reason for less mineralized tissue deposition within channels could be an impairment of the mechanical stability of the formed tissue due to the fluid flow applied. Only recently, it has been shown that impaired mechanical stability of ECM leads to deteriorated tissue organization and decreased tissue growth and reduces the ability of cells to assemble collagen fibres [7]. As a consequence, tissue organization and cytoskeletal changes need to be investigated further for our scaffold model especially by evaluating cytoskeletal differences of cells within the scaffold volume or the channel volume.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations